(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
n recent years, large-scale reforms implemented in the education system of Uzbekistan have led to the introduction of the National Curriculum (NC). This curriculum aims to update state educational standards for all general education subjects and to improve the teaching learning process based on a competency-based approach [1][2]. In the National Program for the Development of School Education for 2022–2026, the full implementation of the National Curriculum, the development of new generation textbooks based on international experience, and the improvement of teachers’ professional qualifications are defined as priority tasks [3]